Design, formulation and evaluation of Aloe vera chewing gum - Aslani, Abolfazl (Adv Biomed Res, 2015)
BACKGROUND: Aloe vera has antioxidant, antiinflammatory, healing, antiseptic, anticancer and antidiabetic effects. The aim of the present study was to design and evaluate the formulation of Aloe vera chewing gum with an appropriate taste and quality with the indications for healing oral wounds, such as lichen planus, mouth sores caused by cancer chemotherapy and mouth abscesses as well as reducing mouth dryness caused by chemotherapy. MATERIALS AND METHODS: In Aloe vera powder, the carbohydrate content was determined according to mannose and phenolic compounds in terms of gallic acid. Aloe vera powder, sugar, liquid glucose, glycerin, sweeteners and different flavors were added to the soft gum bases. In Aloe vera chewing gum formulation, 10% of dried Aloe vera extract entered the gum base. Then the chewing gum was cut into pieces of suitable sizes. Weight uniformity, content uniformity, the organoleptic properties evaluation, releasing the active ingredient in the phosphate buffer (pH, 6.8) and taste evaluation were examined by Latin square method. RESULTS: One gram of Aloe vera powder contained 5.16 ± 0.25 mg/g of phenolic compounds and 104.63 ± 4.72 mg/g of carbohydrates. After making 16 Aloe vera chewing gum formulations, the F(16) formulation was selected as the best formulation according to its physicochemical and organoleptic properties. In fact F(16) formulation has suitable hardness, lack of adhesion to the tooth and appropriate size and taste; and after 30 min, it released more than 90% of its drug content. CONCLUSION: After assessments made, the F(16) formulation with maltitol, aspartame and sugar sweeteners was selected as the best formulation. Among various flavors used, peppermint flavor which had the most acceptance between consumers was selected.